Conti-Brown, Peter, and Sean H. Vanatta. Private Finance, Public Power: A History of Bank Supervision in America - Joseph R. Mason (Journal of Economic Literature, 2026)
Joseph R. Mason of Louisiana State University and BVA Group reviews “Private Finance, Public Power: A History of Bank Supervision in America” by Peter Conti-Brown and Sean H. Vanatta. The Econlit abstract of this book begins: “Presents a positive theory of how bank supervision works today, explaining how through experimentation, error, and the slow building of sometimes redundant, often warring institutions the American system of bank supervision came to be.”